Survey Reveals Frequency of Multiple Resistance to Tribenuron-Methyl, Bensulfuron-Methyl and Halosulfuron-Methyl in Cleavers (Galium aparine L.) - Tiancheng Lou; Ke Wang; Junmin Chen; Jingjing Cao; Tao Gu; Liben Jiang; Yuanlai Lou; Rongxiang Cao; Hongchun Wang (Agronomy, 2022)
Tribenuron-methyl-resistant (TmR) cleavers (Galium aparine L.) have been reported around the major winter wheat farming region in China. From 2017 to 2020, cleavers seeds were collected from wheat production fields across Jiangsu Province to evaluate the frequency and distribution of tribenuron-methyl-, bensulfuron-methyl- and halosulfuron-methyl-resistant cleavers, and to assess the frequency of multiple resistance. Here we report resistance frequency as percent resistance within a population, and resistance distribution as the percentage and locations of populations classified as resistant to a discriminating herbicide dose. From 2017 to 2020, cleavers populations were screened with tribenuron-methyl, bensulfuron-methyl and halosulfuron-methyl. The percentages of tribenuron-methyl-resistant cleavers populations from 2017 to 2020 were 53.33%, 51.52%, 52.38% and 47.17%, respectively; and the percentages of cleavers populations with low tribenuron-methyl resistance were 23.33%, 26.67%, 30.00% and 36.67%, respectively. The percentages of bensulfuron-methyl-resistant cleavers populations from 2017 to 2020 were 36.67%, 39.39%, 35.71% and 33.96%, respectively; and the percentages of cleavers populations had low tribenuron-methyl resistance were 30.00%, 40.00%, 53.33% and 23.33%, respectively. The percentages of halosulfuron-methyl-resistant cleavers populations from 2017 to 2020 were 26.67%, 27.27%, 50.00% and 41.51%, respectively; and the percentages of cleavers population with low tribenuron-methyl resistance were 50.00%, 53.33%, 33.33% and 40.00%, respectively. Finally, 26.67%, 22.22%, 19.05% and 20.75% of cleavers populations had resistance to 2-methyl-4-chlorophenoxyacetic acid sodium (MCPA-Na) from 2017 to 2020, respectively; however, all populations were sensitive to fluroxypyr and carfentrazone-ethyl. This confirmation of multiple resistance in cleavers populations emphasizes the importance of diversity in herbicide sites of action as critical to extending the usefulness of remaining effective herbicides such as MCPA-Na, fluroxypyr and carfentrazone-ethyl for the management of this weed.